SPHINX — A System for Computer-Aided Diagnosis - Fieschi, M.; Joubert, M.; Fieschi, D.; Roux, M. (Methods of Information in Medicine, 1982)
This paper presents a system for computer-aided diagnosis, the SPHINX system, based on methods of inference and pattern matching used in artificial intelligence and on various heuristic features: fuzzy heuristics in relation to the suggestion power of the signs and heuristics based on the costs of complementary investigations. The first application was made in the diagnosis of epigastric pain. Its results are presented and discussed.
Keywords: Computer-Aided Diagnosis; Pattern Matching; Inference Systems; Medical Decision; Epigastric Pain